PaxPortal : a project for Origo - Hallur Hermannsson Aspar 1998-; Hyo-sam Nandkisore 1988-; Reynir Gunnarsson 1983-; Steinar Ísaksson 1995- (2022)
PaxPortal is a B.Sc. final project made by four students in Computer Science at Reykjavík University in cooperation with PaxFlow. PaxFlow is a consumer self-service portal created by Origo. The project goals was to add a user-friendly interface for tourists to enhance their tour experience and make relevant information more accessible. The interface would also be used on ongoing tours to see upcoming destinations, services, listen to a guided audio tour, and communicate with the guide. Alongside that, we implemented a backend for tour operators to create tours and itineraries that is connected to PaxPortal. Origo